Comparison of the distribution and phenology of Arctic Mountain plants between the early 20th and 21st centuries. (23rd July 2021) - MacDougall, Andrew S.; Caplat, Paul; Olofsson, Johan; Siewert, Matthias B.; Bonner, Colin; Esch, Ellen; Lessard‐Therrien, Malie; Rosenzweig, Hannah; Schäfer, Anne‐Kathrin; Raker, Pia; Ridha, Hassan; Bolmgren, Kjell; et al.
Abstract: Arctic plants are adapted to climatic variability, but their long‐term responses to warming remain unclear. Responses may occur by range shifts, phenological adjustments in growth and reproduction, or both. Here, we compare distribution and phenology of 83 arctic and boreal mountain species, sampled identically in the early 20th (1917–1919) and 21st centuries (2017–2018) from a region of northern Sweden that has warmed significantly. We test two compensatory hypotheses to high‐latitude warming—upward shifts in distribution, and earlier or extended growth and reproduction. For distribution, we show dramatic upward migration by 69% of species, averaging 6.1 m per decade, especially boreal woodland taxa whose upward expansion has reduced arctic montane habitat by 30%. Twenty percent of summit species showed distributional shifts but downward, especially moisture‐associated snowbed flora. For phenology, we detected wide inter‐annual variability in the onset of leafing and flowering in both eras. However, there was no detectable change in growing‐season length, relating to two mechanisms. First, plot‐level snow melt data starting in 1917 demonstrated that melt date, rather than vernal temperatures, better predicts plant emergence, with snow melt influenced by warmer years having greater snowfall—warmer springs did not always result in earlier emergence because snowbeds can persist longer. Second, the onset of reproductive senescence between eras was similar, even when plant emergence was earlier by a month, possibly due to intensified summer heat stress or hard‐wired 'canalization' where senescence occurs regardless of summer temperature. Migrations in this system have possibly buffered arctic species against displacement by boreal expansion and warming, but ongoing temperature increases, woody plant invasion, and a potential lack of flexibility in timing of senescence may foreshadow challenges. Abstract : Comparing the distribution and phenology of high‐latitude mountain plants from the early 20th and 21st centuries, we found dramatic upward migration averaging 6.1 m decade −1 . This applied especially to boreal taxa whose expansion reduced arctic montane habitat by 30%. For phenology, there was similarly wide inter‐annual variability in leafing and flowering in both eras. However, growing‐season length was unchanged, relating to deeper and slower melting snowbeds in the modern era that delayed emergence and to inflexibility in senescence regardless of summer climate. Upward range shifts have buffered arctic plants against displacement but ongoing warming, shrubification, and senescence inflexibility foreshadow challenges.